D-Dimensional quantum secret sharing without entanglement. (3rd July 2016) - Qin, Huawang
Abstract: A d -dimensional quantum state secret sharing scheme without entanglement is proposed. In the proposed scheme, the dealer generates a single quantum state in d -dimensional Hilbert space, and performs the Pauli unitary operation on the quantum state according to the private keys of the participants. In the recovery phase, each participant performs the Pauli operation on the quantum state according to his private key, and the last participant will recover the original quantum state. Compared to the existing quantum secret sharing schemes, the main contribution of the proposed scheme is that the quantum state can be shared without the entanglement, so the sharing of the quantum state is more practical.